Socio-cultural and norms factors influencing family planning choices among couples in Ibadan metropolis, Nigeria (2012)
Background: Decisions about the number of children are very important choices among couples in Ibadan. Some socio-cultural and norm factors influence such decisions to a large extent This study established the influence of socio-cultural and norms factors on couples' family planning choices. Method: Couples involved in the study were randomly selected from. 5 different professions in Ibadan, constituted the sample for the study. The two instruments used were author-constructed questionnaires with 0.62 and 0.69 reliability co-efficient, respectively. The data obtained were analyzed using chi-square statistics and multiple regression analysis. Results: The results indicated that significant relationship existed between social and cultural factors (252.959); gender roles (176.849); social networks (95.424); religion (125.742) and local belief factors (205.196). The results further indicated that a combination of the 5 independent variables significantly predicted couples family planning choices yielding a co-efficient multiple Regression (R) of 0.467 and F -ratio of 57.241. The results further revealed that significant relationship existed between each of the independent variables except local belief factors. Conclusion: Based on the results of this finding, it was recommended that those in the helping professions should take cognizance of those variables that have been found to influence family planning choices among couples.